REAL PRODUCTION ACCIDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article foresees incidents, real accidents at work, and that each paragraph of the safety rules should be written on the basis of incidents that have occurred at work, including when assembling or disassembling drilling rigs in an upright position, as well as real accidents, directly at the rig, during drilling with consequences in the form of various accidents and complications.